IMPLEMENTASI HUMAN MACHINE INTERFACE UNTUK PANEL MOTOR CONTROL CENTER PERUSAHAAN KELAPA SAWIT DI PT. SOLUSI INDOSISTEM OTOMAT - Alfabil Arsy Akbar; Arnisa Stefanie; Nono Wahyudi (TEKTRIKA, 2022)
HMI (Human Machine Interface) is widely used in the fields of control and production in the industrial world because the machine that runs a process does not always work well. Using HMI to control and operate a system in industry will be more efficient in terms of time and labor. It will be easy for the operator to track the type of fault through the HMI if the machine has a problem. In the palm oil production process, a control center called the MCC (Motor Control Center) panel is needed to monitor and operate electric motors remotely. This control center is needed by several industries that use electric motors as part of the production process to streamline the operation of electric motors in the field. The trial phase of implementing HMI on the MCC panel is carried out by turning on and off the electric motor, carrying out maintenance, and short-circuiting. The test results produce an accurate response that is equal to 100%. This is indicated by a buzzer that lights up when the electric motor has an error and the colors found on the HMI, such as gray indicating that the electric motor has not started, green indicating that the electric motor is running, orange indicating that maintenance is being carried out on the electric motor, and red indicating a trip on the electric motor. Key Words: Human Machine Interface (HMI), Motor Control Center (MCC) panels, electric motor.